Reconsidering the logic and practice of urban housing intervention: An exploration of urban consolidation policy narratives and their implications for sustainability and equity - Mitchell, Johanna Kate (Curtin University, 2021)
This thesis examines the rhetoric and reality of urban consolidation policy as it is applied in Australia. Focusing on housing innovations implemented in an exemplar sustainable greyfields redevelopment precinct in Fremantle, Western Australia, the research considers the extent to which ‘actually existing’ sustainability and affordability are achieved in practice. The findings reveal the way the current logic and practice of urban housing intervention functions to advance business-as-usual trends and maintain unsustainable and inequitable outcomes.